If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(4 + m) + 2 = m (4 * -5 + m * -5) + 2 = m (-20 + -5m) + 2 = m Reorder the terms: -20 + 2 + -5m = m Combine like terms: -20 + 2 = -18 -18 + -5m = m Solving -18 + -5m = m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -18 + -5m + -1m = m + -1m Combine like terms: -5m + -1m = -6m -18 + -6m = m + -1m Combine like terms: m + -1m = 0 -18 + -6m = 0 Add '18' to each side of the equation. -18 + 18 + -6m = 0 + 18 Combine like terms: -18 + 18 = 0 0 + -6m = 0 + 18 -6m = 0 + 18 Combine like terms: 0 + 18 = 18 -6m = 18 Divide each side by '-6'. m = -3 Simplifying m = -3
| -5(4+m)+2=-3.6 | | 2x*ln(x)+x= | | 1.39x=8.34 | | -5(4+m)+2= | | m-3.75=12.25 | | lnx+ln(x+2)=-1 | | 15x^2-21=0 | | 8x=7-3y9y=-20x+13 | | 15s+22=7m+18 | | (9w-x)(9w-x)= | | w-18=14 | | x^2+2x+e=0 | | 6(8)-2(b)=50 | | (7v-4w)(7v-4w)= | | 2(8)+b=25 | | -3=9x-2 | | 6(5)-2(b)=50 | | 81=36+6x | | 22x-9-16x+4=18x-7-12x+14 | | 2(5)+b=25 | | 49=3w+10 | | -2-5x=2x+12 | | x^2-x-t-5= | | -4x+6+2(x-5)=-2(x+4) | | (3a-3)(a+5)= | | 4y+9-2=0 | | 38.79+4x=110 | | X^2+14x-63=0 | | 4+2x=5x+7-4x | | 2(4y^2-11y+8)=0 | | 2x-4x=9+8x | | 3x-x^2=2 |